Biosynthesis of Silver Nanoparticles and Its Applications - M. Jannathul Firdhouse; P. Lalitha (Journal of Nanotechnology)
Silver nanoparticles possess unique properties which find myriad applications such as antimicrobial, anticancer, larvicidal, catalytic, and wound healing activities. Biogenic syntheses of silver nanoparticles using plants and their pharmacological and other potential applications are gaining momentum owing to its assured rewards. This critical review is aimed at providing an insight into the phytomediated synthesis of silver nanoparticles, its significant applications in various fields, and characterization techniques involved.